Influence of Pd Nanostructures on The Redox Electrochemistry of Ferrocene Monocarboxylic Acid and Ferrocene for Ascorbic Acid Sensing - Singh K.; Maurya K.K.; Malviya M. (My University, 2025)
A/(mV)mA for Fc and Fc-COOH modified electrodes under a similar environment. The current function continuously rises from 10 to 16 mA to 3.63 mA and 1.30 mA to 33.01mAbstract-The effect of Pd nanoparticles geometry has been studied on modifying Fc and Fc-COOH-based electrodes. It has been found to have more reliable results before and after Pd use with Fc-COOH modified electrode. The sensing activity has been performed for ascorbic acid and found quite good results with Fc-COOH-based electrode and surprising results with Pd-modified Fc and Fc-COOH-based electrode, which is further confirmed by performing amperometry titration and observed much high current in case of PdNPs modified Fc-COOH based electrode. The rise in anodic peak current from 14.50.5 A/(mV)mand 6.5 to 13.40.5 respectively. Electrochemical impedance spectroscopy has also been studied, confirming that PdNPs modified Fc and Fc-COOH-based electrodes having low Rct value, the faster charge transfer is compassionate toward ascorbic acid. Transmission electron microscopy, PXRD, and CV have all been used to characterize the nanomaterial with the following major investigation:(i) The average size of PdNPs-1, W to 1.5 kW and 8.3 kW to 1.9 kW. The Rct value decreases from 12.8 k& PdNPs-2 is found 18 nm & 8 nm, (ii) It has been discovered that the palladium content influences both the electrocatalytic effectiveness of novel modified electrode materials and the oxidoreduction electrochemistry of ferrocene and Fc-COOH, and(iii) The modified electrode has an extremely low detection limit for ascorbic acid of <5 μM. © 2023, Center of Excellence in Electrochemistry, Univ. of Tehran. All rights reserved.